Residual amniotic fluid volume predicts the sealing of preterm prelabor rupture of fetal membranes in the pre- and periviable period - Sae Yu; Hirohiko Tani; Yoshitsugu Chigusa; Yosuke Kawamura; Eiji Kondoh; Masaki Mandai; Haruta Mogami (Elsevier, 2023)
Objective: Preterm prelabor rupture of fetal membranes (pPROM) is a leading cause of preterm birth. When pPROM occurs around the pre- and periviable period, the perinatal outcome is unfavorable. However, there have been a few cases in which the leakage of amniotic fluid ceases and the ruptured fetal membranes are spontaneously sealed. Materials and methods: The prognosis of 38 cases of pPROM at less than 27 weeks of gestation in Kyoto University Hospital were studied. The clinical factors related to the sealing of fetal membranes were investigated. Results: Spontaneous sealing was confirmed in five patients (13%), and sealing occurred within 14 days of pPROM. Women in the no sealing group delivered at 26.3 ± 0.5 weeks of gestation, whereas women in the sealing group delivered at term at 38.8 ± 0.4 weeks (p < 0.0001). The maximum vertical pocket (MVP) of amniotic fluid at the time of pPROM diagnosis was 2.2 ± 0.3 cm in the no sealing group and 3.8 ± 0.5 cm in the sealing group (p = 0.043). All cases of sealing occurred when the MVP at diagnosis was more than 2 cm, and there were no cases of sealing if the MVP at diagnosis was less than 2 cm. In addition, the value of C-reactive protein at ROM was less than 0.4 mg/dL in all cases in the sealing group. Conclusion: The residual volume of sterile amniotic fluid at the onset of pPROM may predict the possibility of fetal membrane sealing.